Excellent strength-ductility combination in nickel-graphite nanoplatelet (GNP/Ni) nanocomposites - Borkar, Tushar; Mohseni, Hamidreza; Hwang, Junyeon; Scharf, Thomas W.; Tiley, Jaimie S.; Hong, Soon H.; Banerjee, Rajarshi (ELSEVIER SCIENCE SA, 2015)
While multiple recent reports have demonstrated enormous enhancements in yield strength in metal matrix nanocomposites reinforced with carbon nanotubes and graphite nanoplatelets (GNP), such composites typically exhibit drastic reductions in tensile ductility. Mechanical mixing of nickel (Ni) powders and GNP powders, followed by spark plasma sintering (SPS), has been used to develop a new class of GNP/Ni nanocomposites that exhibit huge enhancements in tensile yield strength while preserving good ductility. Thus, a Ni-1GNP (1 vol.% GNP) nanocomposite exhibited a tensile yield strength of 370 MPa (about 2.5 times of SPS processed monolithic nickel similar to 160 MPa) and an elongation to failure similar to 40%. Interestingly, while a higher volume fraction of GNPs, such as Ni-2.5GNP (2.5 vol.% GNP) exhibited an enhancement in tensile yield strength due to grain refinement, there was a significant reduction in ductility similar to 10%, primarily due to agglomeration of GNPs. The enhancement in the tensile strength and ductility of the Ni-1GNP nanocomposite can be attributed to combined effect of homogeneous dispersion of GNPs and grain refinement, the relative influence of each of these effects has been quantitatively assessed in this paper. Additionally, the strong metal-GNP interfacial bonding helps effectively transfer load across the GNP/metal interface during tensile deformation. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: ENHANCED MECHANICAL-PROPERTIES; PLASMA SINTERING SPS; GRAPHENE; COMPOSITES; COPPER; MICROSTRUCTURE; CONSOLIDATION; FABRICATION; PRESSURE; BEHAVIOR